SELF- REGULATED STRATEGY DEVELOPMENT (SRSD) METHOD: EFFECTS IN THE STUDENTS’ WRITING SKILL. - Dzakiyatul Lutfiah Dahlan (English Education Department Slamet Riyadi University Surakarta, 2019)
This study was conducted to know the significant difference in students’ writing skill using SRSD method and to know which groups get better achievement in writing skill at the tenth grade of MAN 1 Surakarta. The researcher used experimental research which was conducted from April until May 2018. The data were collected by using written test. The results of tests were analyzed by using normality, homogeneity, t- test independent, and t-test non independent. The first result showed that there was significant difference in students’ writing skill between experimental class who was taught by using SRSD method and control class who was taught using conventional method. It could be proven from the result of t- test independent with the value of t was 1.78 of pre-test and the value of t of post-test was 1.74. It was higher than t table (α 0.05) = 1.67. The second result showed that experimental group gets better achievement than control group. It was shown by the mean of post- test of experimental (73.61) was higher than the mean score of control class (70.57). In addition, the computation of t-test non independent showed that t value of SRSD method (10.37) was greater than t value of conventional method (9.05) with α = 0.05 and df = 26. Keywords: Self- Regulated Strategy Development, SRSD Method, Experimental Research. Writing Skill